The effective use of remainder term estimation in the limit theorems - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2003)
We investigate the asymptotic behavior of mean value of multiplicative arithmetic function from the class M1(G). In the present paper the asymptotic formula under special condition on prime elements of Knopfmacher’s semigroup G is obtained.